PENGEMBANGAN MEDIA DIGIBOOK PADA MATERI ALJABAR UNTUK MENGOPTIMALKAN KEMAMPUAN NUMERASI MATEMATIS - Mulyana, Pepy Risman; Aripin; Lestari, Puji (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
In an effort to support literacy and numeracy empowerment programs, the government abolished the National Exam and replaced it with the Minimum Competency Assessment and Character Survey. There are two basic competencies measured in the AKM, namely literacy and numeracy. The numeracy skills of junior high school students are still not satisfactory, special efforts are needed to improve numeracy skills that keep pace with the times. Currently, education has been integrated with technology, both in terms of learning and the use of media. The underlying factor of this study is that there is a significant decrease in the Education Report Card, in the numeracy indicator on algebraic competence. This research aims to produce digibook media on algebra materials to optimize students' numeracy skills. This research was carried out at SMPN 3 Kawali using the R&D (Research and Development) method with the ADDIE model. There are five stages, namely the Analysis stage, the Design stage, the Development stage, the Implementation stage and the Evaluation stage. Data collection techniques through observation, interviews, validation sheets of material and media experts, student response questionnaires and numeracy ability tests. Based on the results of research, development and discussion, validation results were obtained from material experts and media experts that the digibook in this algebra material was declared valid with the category "very feasible to use". The user's response to the digibook on this algebra material is positive with the category of "excellent". Based on the results of research, development and discussion, it can be concluded that this study produces a digibook product that is very suitable for use in learning algebraic materials with an effectiveness quality (effect size) of 2.28350953 > 1.00 in the "strong effect" criterion.